Thrust areas in agricultural engineering education and research in Malaysia - Ahmad, Mohammad Nur; Abang Ali, Abang Abdullah (1985)
Malaysia is a leading producer of palm oil and rubber and is presently intensifying production activities in various types of food crops. Modernization of the agricultural sector is necessary to optimise production and to improve working condition. Expertise at various levels of agricultural production ranging from land preparation to harvesting and post-harvest operations is needed. Research and development work in agricultural engineering is being directed towards solving the immediate problems of this sector.